Gaps in mangrove science - Maxwell, Gordon S. (Food Agricultural Sciences and Technology, 2015)
As tidal forest found on tropical and subtropical coastlines, mangroves have long attracted scientists, yet gaps in our knowledge remain. Perhaps refl ecting the many and variable ways in which ecological conditions exist and factors may interact in the intertidal environment, uncertainties and debate are evident at mangrove conferences. Even core issues such as salinity tolerance and what constitutes a ‘true’ mangrove endure. This paper seeks to review the gaps in mangrove science and do so in a way that may stimulate further research. Aspects of mangrove fl ora such as ‘true’ vs. ‘associate’ mangrove and the species concept open the discussion. Some very basic biological processes such as age and wood, phenology and root:shoot biomass allocations follow. These lay the foundations for a survey of ecological processes and challenges including salinity tolerance, soil redox conditions, temperature limitations, propagule dispersal, mineral cycling and mangroves as carbon sinks and land builders. The older topic of mangrove succession and the very neglected question of pathogenic Phytopthora in mangroves are also examined. Collectively, the above biological and ecological gaps in our knowledge provide a platform on which mangrove goods and services and applied sciences can be evaluated. Into these topic areas come the urgently needed economic valuations of mangrove resources in fi sheries and coastal protection, together with their largely unheralded potential as a bank of biomedical and bioactive compounds. Finally, contentious issues such as using (or mis-using) mangroves as sinks for industrial waste and how much biodiversity is needed to maintain functionality in mangrove eco-restoration are examined. Some apparently small but nevertheless attractive topics like tiger and dolphin conservation and mangroves as food also appear and serve to illustrate the sometimes subtle interconnections within mangrove ecosystem science.